Sleep Deprivation and Cognitive Performances: Methodological Processes towards Suggestive Mechanisms - Tengku Muhammad Ariff, Raja Hussin; Ahmad Zubaidi, A.latif; Lua, Pei Lin (2018)
Human performances are interdependent on sleep-wake rhythm, driven by circadian cycle and are naturally functional in adaptation to day-night differences in the environment. This review explained and explored the effect of Sleep Deprivation (SD) on cognitive performances. The effect of sleep deprivation (both total and partial) on attention, memory, visuo-motor performances, motor functions, decision making, response inhibition, etc. are critically discussed to be effective beside the role of methodological concerns in carrying out SD studies. There is a special need of discussing and evaluating the effect of SD on cognitive pattern in Easter, South Eastern and African regions as per cultural and norms to be more specific with response towards methodologies.